Persepsi Mahasiswa terhadap Pendidikan Etika Profesi Akuntan dalam Pendidikan Akuntansi - Achdy Muhadis; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2022)
This study describes the perception of stakeholders about the importance of accounting profession ethics education. The purpose of this study was to look at the differences in perceptions in the views of students, both those who have taken ethics courses and those who have not, and to see from the gender differences of these students. In contrast to previous studies which only looked at conceptual differences between students and lecturers, this study adds to the perceptions of graduates. This study uses a purpose sampling method and a survey method through the distribution of questionnaires. The results of this study (1) indicate that there is no difference in perception among interested parties about the importance of professional ethics education for accountants. (2) There is no difference in perception about the importance of ethics education in the accounting profession between men and women. (3) There is no difference in perception between students who take or do not take accounting profession ethics education courses.